Dampak Covid 19 Terhadap Praktik Jual-Beli: - Sappeami, Sitti Aisyah. M (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2020)
The Corona virus pandemic exploited by irresponsible elements. They do a cunning business strategy, which is to hoard goods, in fiqhi terms known as iḥtikār. In the Islamic view, iḥtikār is a prohibited business practice and will be met with a painful punishment in the afterlife. The purpose of this paper is to provide an understanding about the impact of COVID 19 on the practice of buying and selling (iḥtikār). This paper uses qualitative research methods in the form of library reseach using the shar'i approach. From this study it can be concluded that the behavior of hoarding goods with the aim of reselling them at high prices to obtain large profits. In Islamic Shari'ah, iḥtikār‘s law is haram because it contains elements that harm others. This is very clearly stated in QS al-Humazah/109: 1-2 and punished by sin as stipulated in the hadith of the Messenger of Allah.